Helicopter hover ceiling improvement possibilities and its limits with an electric tail-rotor - Kallur-Krishnamoorthy, R.; Kramer, P. (My University, 2021)
For conventional helicopters with single main-rotor and fixed-speed tail-rotor whose hover ceiling is limited by the tail-rotor thrust, variable speed electric tail-rotors could potentially improve hover ceiling by operating at higher rotor speed. On the basis of a 2D-panel method code and transonic small disturbance theory for airfoil section coefficients, and blade-element and momentum (BEM) theory model, the tail-rotor performance is analysed for higher rotor speeds compared to base configuration. Results are presented for an example existing helicopter for hover out-of-ground effect (OGE) with maximum take-off weight (MTOW) conditions. The results confirm that compressibility effects at the tip-section is the major limitation for operating at higher rotor speeds. Combined with the thrust and power balance for the tail-rotor and helicopter powerplant respectively, hover ceiling improvement is quantified. In spite of the limited speed increase possibility due to compressibility effects a noticeable improvement to hover ceiling is made possible with the variable speed electric tail-rotor configuration.